Does ability to walk reflect general functionality in inflammatory neuropathies?. Issue 2 (1st June 2016) - Draak, Thomas H. P.; Gorson, Kenneth C.; Vanhoutte, Els K.; van Nes, Sonja I.; van Doorn, Pieter A.; Cornblath, David R.; van den Berg, Leonard H.; Faber, Catharina G.; Merkies, Ingemar S. J.; ,
Abstract: The "ability to walk" is considered a benchmark for good clinical recovery and prognosis, particularly in patients with Guillain‐Barré syndrome (GBS) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). However, it has never been determined whether being "able to walk" represents general functionality. The purpose of this study was to examine whether the ability to walk outside independently reflects general functional improvement in patients with GBS, CIDP, and gammopathy‐related neuropathy (MGUSP). A total of 137 patients with newly diagnosed (or relapsing) GBS (55), CIDP (59), and MGUSP (23) were serially examined (1‐year). Predefined arbitrary cut‐offs (so‐called patients' Functional‐Acceptable‐Clinical‐Thresholds [FACTs]) were taken at the 50th, 75th, and 90th percentile of the Inflammatory‐Rasch‐built‐Overall‐Disability‐Scale (I‐RODS © ). We determined the proportion of patients able to walk outside independently that reached the postulated cut‐offs. A mean total of 85%, 39%, and 12% of all patients able to walk reached 50th, 75th, and 90th percentile thresholds, respectively. These findings were not neuropathy type related. Our findings show that assessing only one construct of functionality (e.g., walking ability) does not reflect the full scope of daily/social functional deficits perceived by patients. The ability to walk shows a patient is doing better, but not necessarily doing well. The I‐RODS © bypasses these limitations.